Holistic Design of Energy Pile Bridge Deicing System With Ontology-Based Multiobjective Decision Making - Zhang, Peng; Cui, Chunyi; Li, Chaoji; Zhang, Cheng; Liu, Hailong (Frontiers in Materials, 2021)
Even though the energy piles have been applied for the bridge de-icing system, the traditional design approach is commonly a single-domain and objective-oriented method, and consequently lacking means to comprehensively consider all the relevant factors, such as life-cycle cost, investment payback cycle, carbon emissions, etc. This paper presents a holistic design scheme for the energy pile de-icing system of bridge decks. In this paper, a holistic designing tool, namely OntoBDDS, was developed based on ontology method and SWRL rules. It can automatically provide financial, safety, and heat flux information for designers to evaluate and optimize the design scheme of a de-icing system in the early design stage of a bridge. After semantic and syntactical validation of the OntoBDDS system, a case study was also conducted to demonstrate how to leverage knowledge query to provide a series of design alternatives autonomously through considering different design parameters. This case study also verified the practicability and feasibility of the OntoBDDS holistic decision-making system and indicated its potential to be applied for other engineering problems when dealing with multi-objective holistic design making.